Dampak Pasca Pemekaran Daerah terhadap Kesejahteraan Masyarakat: Studi kasus: : Kabupaten Musi Rawas Utara Provinsi Sumatera Selatan - Diah Ayu Sholeha; Zhahara Dwi Amanda; Diko Ardiansyah; Paris Likuwatan; Nur Maria Magdalena; Yusnike Yusnike (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2024)
This research discusses the impact of post-regional expansion on community welfare, with a case study in North Musi Rawas Regency, South Sumatra Province. Regional expansion aims to improve public services and community welfare through decentralization. This research method uses a qualitative approach with library research analysis. The research results show that expansion has succeeded in reducing unemployment rates, increasing access and quality of public services, as well as improving education and health facilities. However, there are challenges such as decreasing agricultural productivity and low community participation. Overall, regional expansion can be an effective tool for improving community welfare, provided there are appropriate policies and active participation from all elements of society.